Students as catalysts for curricular innovation: A change management framework. (3rd May 2020) - Burk-Rafel, Jesse; Harris, Kevin B.; Heath, Jacqueline; Milliron, Alyssa; Savage, David J.; Skochelak, Susan E.
Abstract: Introduction: The role of medical students in catalyzing and leading curricular change in US medical schools is not well described. Here, American Medical Association student and physician leaders in the Accelerating Change in Medical Education initiative use qualitative methods to better define student leadership in curricular change. Methods: The authors developed case studies describing student leadership in curricular change efforts. Case studies were presented at a national medical education workshop; participants provided worksheet reflections and were surveyed, and responses were transcribed. Kotter's change management framework was used to categorize reported student roles in curricular change. Thematic analysis was used to identify barriers to student engagement and activators to overcome these barriers. Results: Student roles spanned all eight steps of Kotter's change management framework. Barriers to student engagement were related to faculty (e.g. view student roles narrowly), students (e.g. fear change or expect faculty-led curricula), or both (e.g. lack leadership training). Activators were: (1) recruiting collaborative faculty, staff, and students; (2) broadening student leadership roles; (3) empowering student leaders; and (4) recognizing student successes. Conclusions: By applying these activators, medical schools can build robust student–faculty partnerships that maximize collaboration, moving students beyond passive educational consumption to change agency and curricular co-creation.